Music from 0 to 3 years old (Journal of Parents and Teachers, 1995)
Activities are presented for babies to differentiate sound and silence through music, sound toys and stories. The activities are suitable from the age of 3 months and encourage the perception of silence and touch.
Keywords: music and education; sound; silence; touch